Water Use by Inland Aquaculture in Thailand: Stakeholder Perceptions, Scientific Evidence, and Public Policy - Louis Lebel (2019)
© 2019, Springer Science+Business Media, LLC, part of Springer Nature. This paper assesses the significance of stakeholder discourses on uses of water by aquaculture for public policy. Our discourse analysis focuses on the experiences with inland aquaculture in Thailand, drawing from interviews with stakeholders, and evidence in public documents such as newspapers and television news reports. A key finding is that fish farms suffer significant losses from polluted run-off entering water bodies where fish are grown. Mass mortality events in river cage culture, in particular, attract media attention and are the core of the aquaculture-as-victim discourse. Fish farms are also adversely impacted by river management and current water allocation policies. Inland shrimp farming has received more negative media and scientific attention than fish farming, and is the focus of the aquaculture-as-villain discourse. A third, aquaculture-as-benign discourse, is used widely to describe fish pond culture, and more rarely to promote aquaculture in low-quality water bodies or as part of integrated nutrient and waste re-use farming systems. The findings strongly imply that aquaculture farmers should be included as a stakeholder in the management of watersheds and rivers, as well as the negotiation and allocation of water resources. They also suggest a need for aquaculture development policies to pay closer attention to water quality and allocation issues.